2009
DOI: 10.5194/bg-6-2957-2009
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of CO<sub>2</sub> and water exchanges over three agroecosystems in South-West France

Abstract: Abstract.During the last few decades, many studies have been performed to determine water and carbon budgets of broadleaf and deciduous forests, crops and grasslands. However, since most measurements have been made in different regions and at different periods, it is difficult to compare the results directly. In order to evaluate accurately the respective contribution of various agroecosystems to global water and carbon exchanges, it is necessary to compare data obtained in similar climatic and weather conditi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
4
9
0
1
Order By: Relevance
“…We hypothesize that this difference was a consequence of a less intense soil respiration in croplands during summer. From simultaneous eddy covariance measurements over pine forests and maize croplands of the study area, Stella et al (2009) confirmed that ecosystem respiration was lower in croplands than in forests over the whole year. However, Stella et al (2009) also showed that ecosystem respiration was larger during the growing season of the maize, because of increased of soil respiration in response to the higher soil water content caused by irrigation.…”
Section: Dynamic Of O 2 Doc Dic and δ 13 C-dic In Groundwater: A Csupporting
confidence: 54%
See 3 more Smart Citations
“…We hypothesize that this difference was a consequence of a less intense soil respiration in croplands during summer. From simultaneous eddy covariance measurements over pine forests and maize croplands of the study area, Stella et al (2009) confirmed that ecosystem respiration was lower in croplands than in forests over the whole year. However, Stella et al (2009) also showed that ecosystem respiration was larger during the growing season of the maize, because of increased of soil respiration in response to the higher soil water content caused by irrigation.…”
Section: Dynamic Of O 2 Doc Dic and δ 13 C-dic In Groundwater: A Csupporting
confidence: 54%
“…From simultaneous eddy covariance measurements over pine forests and maize croplands of the study area, Stella et al (2009) confirmed that ecosystem respiration was lower in croplands than in forests over the whole year. However, Stella et al (2009) also showed that ecosystem respiration was larger during the growing season of the maize, because of increased of soil respiration in response to the higher soil water content caused by irrigation. In forest sites, groundwater pCO 2 increases during the summer because soil CO 2 diffuses downward and then is dissolved into the water table Tsypin and Macpherson, 2012).…”
Section: Dynamic Of O 2 Doc Dic and δ 13 C-dic In Groundwater: A Csupporting
confidence: 54%
See 2 more Smart Citations
“…The flux data both for surface energy balance and CO 2 exchange, obtained from several vegetation types proved essential data for calibrating the land surface schemes (e.g. Ahmadov et al, 2007) and for investigating and understanding fundamental differences in sequestration capacities Jarosz et al (2009) and Stella et al (2009). While observations on additional sites were only obtained during the experimental campaigns, the backbone of sites was part of the CarboEurope network of sites and these potentially allow for further studies involving question of representability and interannual variation.…”
Section: Discussionmentioning
confidence: 99%